2019
DOI: 10.1002/1873-3468.13368
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo protease activity assay for investigating the functions of the Escherichia coli membrane protease HtpX

Abstract: Escherichia coli HtpX is an M48 family zinc metalloproteinase located in the cytoplasmic membrane. Previous studies suggested that it is involved in the quality control of membrane proteins. However, its in vivo proteolytic function has not been characterized in detail, mainly because the physiological substrates have not been identified and no model substrate that allows sensitive detection of the protease activity is available. We constructed a new model substrate of HtpX and established an in vivo semiquant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…We also observed an upregulation of genes that are involved in phage shock protein operon (pspA, pspB, pspC, and pspE). Yoshitani et al (2019) found that htpX along with ftsH lyse the abnormal IM proteins of EHEC (Yoshitani et al, 2019). Besides, Shimohata et al (2002) reported that the accumulation of misfolded proteins in the IM may occur due to the inefficiency or loss of htpX or ftsH which further activates Cpx stress response proteins located in periplasmic space (Shimohata et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed an upregulation of genes that are involved in phage shock protein operon (pspA, pspB, pspC, and pspE). Yoshitani et al (2019) found that htpX along with ftsH lyse the abnormal IM proteins of EHEC (Yoshitani et al, 2019). Besides, Shimohata et al (2002) reported that the accumulation of misfolded proteins in the IM may occur due to the inefficiency or loss of htpX or ftsH which further activates Cpx stress response proteins located in periplasmic space (Shimohata et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were visualized by a Lumino image analyzer LAS-4000 mini (Cytiva) using ECL (enhanced chemiluminescence) or ECL Prime Western Blotting Detection Reagents (Cytiva). Rabbit polyclonal anti–hemagglutinin (HA) [HA-probe (Y-11), Santa Cruz Biotechnology], anti–maltose-binding protein (MBP) ( 57 ), anti- Ec RseP ( 19 ), and anti-SecB ( 21 ) antibodies and rat monoclonal anti-PA antibodies ( 58 ) were used for immunoblotting. Also, for detection of His-tagged proteins, anti-His antibodies from the Penta-His HRP Conjugate Kit (Qiagen) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were visualized by Lumino image analyzer LAS-4000 mini (Cytiva) using ECL or ECL Prime Western Blotting Detection Reagents (Cytiva). Rabbit polyclonal anti-HA (HA-probe (Y-11), Santa Cruz Biotechnology), anti-MBP ( 62 ), anti- Ec RseP ( 19 ) and anti-SecB ( 21 ) antibodies, and rat monoclonal anti-PA antibodies ( 63 ) were used for immunoblotting. Also, for detection of His-tagged proteins, anti-His antibodies from the Penta-His HRP Conjugate Kit (Qiagen) were used.…”
Section: Methodsmentioning
confidence: 99%